The Effect of Organizational Culture, Sharing Knowledge, and Intention to Share on Competency through Organizational Commitment As a Mediating Variable - Eka Desy Purnama; C. Catur Widayati (Universitas Mercu Buana, 2023)
Objectives: The phenomenon in this study is that the skills possessed by employees are still not optimal, as well as the lack of knowledge of banking products that must be mastered by front liners, especially in the teller department so that the impact on not achieving predetermined business targets. The existence of complaints recorded through the call center or submitted directly to the branch office indicates that the level of customer satisfaction has not been optimally achieved. The purpose of this research is to find out the significance of the influence of organizational culture, sharing knowledge, as well as the intention to share competencies through organizational commitment as an intervening variable at PT BCA South Tangerang Region.Methodology: In this study, the population of this study is permanent employees and the number of samples used is 99 respondents. Data collection techniques used interviews and questionnaires. The method of data analysis is using the PLS program.Finding: In this study, it is found that to increase organizational competence as a whole, intention to share, knowledge sharing, and organizational culture are needed. To increase customer satisfaction with bank service, it is also necessary to have a good commitment from employees to the organization. Conclusion: For further research, it is suggested to examine other private banks that face the same problem which may produce different findings; conduct research on relatively similar objects, such as leasing which also faces the same problem, and add the concept of organizational citizenship behavior (OCB), motivation, engagement, work stress, and others for further research.